Efikasi Diri Lanjut Usia di Rumah Pelayanan Sosial Lansia: Studi Kasus Penerapan Metode Mauidhoh Hasanah (Self-Efficacy of the Elderly in Elderly Social Service Home: A Case Study of Method Application Mauidhoh Hasanah) - Nihayah, Ulin; Zahir Luthfil Khakim, Muhammad (Program Studi Psikologi Islam (IAIN) Kediri, 2025)
This study aims to analyze the implementation of religious guidance based on the Mauidhoh Hasanah method at the Elderly Social Service House (RPSL) Pucang Gading Semarang and its impact on the elderly's self-efficacy. The Mauidhoh Hasanah method emphasizes wise advice and a personal approach to provide spiritual support tailored to the needs of the elderly. A qualitative approach with a case study method was used in this research. Data collection was conducted through participatory observation, semi-structured interviews, and documentation, which were analyzed thematically to ensure data validity. The results show that the Mauidhoh Hasanah method is effective in fostering elderly self-efficacy. Improvements were seen in the elderly’s confidence in fulfilling religious obligations, emotional regulation, and optimism in facing life challenges. Supporting factors for success include a personal approach, the use of simple language, and materials relevant to daily life. Identified barriers include the elderly’s physical limitations and the limited time available for the guidance sessions. The conclusion of this study indicates that the Mauidhoh Hasanah method has a significant positive impact on the spiritual and psychological well-being of the elderly, making it a relevant religious guidance model to be applied in social care institutions